2019
DOI: 10.1186/s13052-019-0760-5
|View full text |Cite
|
Sign up to set email alerts
|

Early onset retinal dystrophies: clinical clues to diagnosis for pediatricians

Abstract: IntroductionInherited retinal dystrophies are major cause of severe progressive vision loss in children. Early recognition and diagnosis are essential for timely visual rehabilitation during the appropriate stages of the visual development, as well as for genetic diagnosis and possible gene therapy. The aim of this study is to characterize a pattern of the initial visual symptoms, which could help the pediatricians and the primary care providers to suspect an inherited retinal disorder in its early stageMethod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Patients reported to have experienced the first signs of visual impairment during their early childhood. As also shown in other studies, 15 parental caregivers were able to reliably recognize some of the earliest RPE65 -related IRDs signs (light gazing, lack of eye contact, night blindness). Since confirming the clinical diagnosis may be challenging in early childhood, parental observation may be crucial for the clinical suspicion, and it may also help pediatricians and ophthalmologists to identify – or suspect – the condition and early refer patients to centers specialized in IRDs.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Patients reported to have experienced the first signs of visual impairment during their early childhood. As also shown in other studies, 15 parental caregivers were able to reliably recognize some of the earliest RPE65 -related IRDs signs (light gazing, lack of eye contact, night blindness). Since confirming the clinical diagnosis may be challenging in early childhood, parental observation may be crucial for the clinical suspicion, and it may also help pediatricians and ophthalmologists to identify – or suspect – the condition and early refer patients to centers specialized in IRDs.…”
Section: Discussionsupporting
confidence: 80%
“… 7 , 8 While IRDs management remains mainly support-oriented with a focus on monitoring, education, and counseling, 3 gene therapy represents a novel potential treatment 3 , 9–11 as no treatments yet could slow or stop the progression of sight loss. 12 Since the age of onset ranges from early childhood to middle age, a timely detection of IRDs 13 , 14 and an optimal multidisciplinary management 15 can significantly influence the improvement of the patient’s quality of life and offer therapeutic perspectives: an early diagnosis is critical to proper visual rehabilitation, as well as for genetic diagnosis and counseling and gene replacement therapies. 16 , 17 In particular, referral to highly specialized centers ensures multidisciplinary and personalized care, 18 while a genetic diagnosis is critical to establish eligibility for an optimal gene therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, nystagmus was the first symptom reported by parents if the disease onset was before six months of age. 11 Another Chinese study of 136 patients with a specific type of nystagmus (pendular low amplitude, high frequency) showed that 52% had abnormal fundi and 34% had genetic mutations causing various inherited retinal dystrophies. 12 Nystagmus has been reported in several specific cone and rod dystrophies, including congenital stationary night blindness, achromatopsia, LCA, Bardet-Biedl syndrome, Joubert's syndrome, and Alstrom's syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…In preverbal children, abnormal visual behavior and nystagmus observed and reported by the parents should prompt an appropriate ophthalmological workup for IRD. 7…”
Section: Disease Awareness and Educationmentioning
confidence: 99%